Message from Editor-in-Chief - Maohua, Wang; Ruan, Roger (International Journal of Agricultural and Biological Engineering, 2009)
We had a very successful launch of IJABE in 2008. Since then the journal has received manuscript contributions from many authors and published over 21 papers on a wide range of topics in addition to others. IJABE was included in Chemical Abstracts soon after the first issue and in CAB Abstracts after the second issue. Both Chemical Abstracts and CAB Abstracts are major academic publication indexing databases. In addition, IJABE has also been listed by Open J-Gate, the world